2016
DOI: 10.1093/eurpub/ckw123
|View full text |Cite
|
Sign up to set email alerts
|

Searching for sustainability within public health policy: insights from an injury prevention perspective

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It must be mentioned as one of the limitations of the study that not many references were found in the literature [22] that would allow us to contrast the results obtained with the Safe Fall programme with another on a regional, state, or international level and to enable a meta-analysis of data.…”
Section: Discussionmentioning
confidence: 99%
“…It must be mentioned as one of the limitations of the study that not many references were found in the literature [22] that would allow us to contrast the results obtained with the Safe Fall programme with another on a regional, state, or international level and to enable a meta-analysis of data.…”
Section: Discussionmentioning
confidence: 99%
“…The sustainability of public health programs is poorly addressed in global policies [3]. Strengthening national and international sustainability policies and incorporating them into public health planning frameworks can create an environment that better enables local programs.…”
Section: Introductionmentioning
confidence: 99%